PENGARUH PROFITABILITAS DAN PERTUMBUHAN ASET SERTA UKURAN PERUSAHAAN TERHADAP LEVERAGE PADA PERUSAHAAN SEKTOR PERTANIAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - RINDHY NILA SARI; RUSDIAH ISKANDAR; FIBRIANI NUR KHAIRIN (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2016)
This study aimed to determine the effect of profitability, asset growth and size of the company to leverage on the agricultural sector companies listed on the Indonesian stock exchanges. In this population is the agricultural sector company listed on the Indonesian stock exchange in term of 2012 – 2014. While the sample is determined by purposive sampling method to obtain 11 companies sample. The type of data used are secondary data obtained from www.idx.co.id. The analysis method used is multiple linear regression. analysis based on the results of multiple  linear regression analysis with significance level of 5%.The result of this study concluded profitability (ROA) negative effect and significant on leverage, asset growth significant effect on leverage and company size does not significantly affect the leverage.Keywords: leverage, profitability, asset growth and size.